Corrosion-preventing method of reinforced concrete structure under sour corrosion environment - LIU WENLIANG; HAO DAWEI; PEI FUBO; TIAN WENCHUN; NIU BINBIN; ZHANG ZHONGSHENG (2017)
The invention discloses a corrosion-preventing method of a reinforced concrete structure under the sour corrosion environment. The method is characterized by comprising the following steps that a, the corrosion condition of underground water of a designed project to reinforced concrete is surveyed; b, prestressed concrete pipe pile and concrete pipe pile construction and quality inspection and acceptance are selected in pile foundation engineering; c, the surface of the concrete structure is subject to corrosion-prevention treatment; d, backfill treatment is carried out. The corrosion-preventing method of the reinforced concrete structure under the sour corrosion environment has the beneficial effects of effectively reducing corrosion of corrosive underground water to the reinforced concrete, improving durability of the reinforced concrete, ensuring the construction proceed, and reducing the construction cost. 种钢筋混凝土结构在酸性腐蚀环境下的防腐方法，其特征在于包括以下步骤：a.调查拟建项目地下水对钢筋混凝土腐蚀情况，b.桩基工程选用预应力混凝土管桩和混凝土管桩施工及质量检查验收，c.混凝土结构表面防腐处